Digital Storytelling: An Attractive Media to Teach Narrative Text in Speaking Class - Muhammad Mujtaba Mitra Zuana (Alsuna: Journal of Arabic and English Language, 2018)
In 21st century, a huge change happens in which students prefer to learn by using digital technology. Some interesting digital technology devices are expected to apply by the teachers in the process of teaching and learning. One of the technologies that can be used in teaching activities is digital storytelling. The teachers can combine both personal narratives and the use of technology in their English classes. Thus, this study was conducted to describe the implementation of digital storytelling, the students’ responses to the use of digital, and the students’ digital storytelling works after implementing the media in the teaching and learning process. The design of this research was a descriptive qualitative. The researcher used Field notes, students’ digital storytelling, and interview as instruments of collecting data. The researcher used data condensation, data display, and drawing conclusion to analyze the data. From Some findings of this study, the media can be considered as very attractive. They are eager to speak English during the process of video production. The media has significant role to decrease the students’ anxiety in speaking. It has empowered them to make the digital storytelling video either inside or outside the classroom. At last, the students’ ability is varied. The speaking criteria from O’Malley and Pierce’s scoring rubric is not reached by all students.